The influence of fiscal rules on local government: evidence from Brazil - Santos, Rafael Cavalieri dos (2024)
This study analyzes the effects of the Lei de Responsabilidade Fiscal (LRF) on Brazilian municipalities. More specifically, the LRF established that municipalities could not spend more than 60% of their revenues on personnel expenses. We employed quasi-experimental methods, specifically Regression Discontinuity and Event-Study, to examine the impact of the LRF\'s threshold on municipal fiscal behavior, focusing on outsourced services and investments. Our main result indicates that non-compliant municipalities increased their spending on outsourced services as a proportion of revenues and expenditures by approximately 11% after LRF, compared to the control group.